Association of Erythropoietin, Adiponectin and Leptin levels with Anemia in uremic diabetic patients (Under hemodialysis): - Al-Rubaâe, Salim M.; Daoud, Munaf S.; Al-Kadium, Tahrir E. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: End stage renal disease in patients with diabetes mellitus has been called a medical catastrophe of worldwide dimensions .It was recognized that anemia is a complication of diabetes, particularly in patients with diabetic kidney diseases. The purpose of the present study is to determine whether erythropoietin, adiponectin, and leptin levels correlate with anemia in uremic diabetic patients (under hemodialysis).Patients and Methods: The studied groups were comprised of (30) diabetic patients(9 patients with type1 and 21 type2 diabetes) with renal failure (group2) who had been under hemodialysis compared with (30) healthy controls (group1). Blood film was obtained in addition to blood tests include fasting serum glucose (FSG), glycosylated hemoglobin (A1c), insulin, urea, creatinine, uric acid, estimated glomerular filtration rate (eGFR), serum erythropoietin (EPO), Adiponectin (ADPN),and leptin.Results: It was found that uremic diabetic patients in group2(G2) had higher FSG, A1c, insulin and higher levels of urea, creatinine, uric acid and lower levels of eGFR when compared to healthy controls (P